The elusive divide between tacit collusion and concerted practices - Ali, RK (2019)
Sellers in oligopolistic markets can cooperate in ways that diverge from the orthodox vision of competition. It is a bigger issue, however, that there are also deviations in vision between competition law and economics on some basic categories. Foremost among these is the grey zone between two of the practices this thesis studies: tacit collusion and concerted practices. The two disciplines’ divergent interpretations of the interaction between sellers permeate the canon of enforcement practice, case law, and academic thinking. In more clear-cut instances, like cartels, this underlying divergence is inconsequential. However, the more ambivalent the practice, the more glaring the divergence becomes. Blind spots ensue because the two disciplines look at the problem from different angles. Using the prism of natural and artifical transparency, this thesis explores these blind spots, which feature throughout the history of competition law but appear to be expanding as technology and the means of interaction evolve from human intution to artificial intelligence (“AI”). Novel forms of coordination may expand the scope of tacit collusion. Here, the competition toolkit will likely prove adaptable. Yet, as long as human actors remain involved in the process, certain social codes and mutual perceptions of the market and will continue to enhance transparency in ways that competition law struggles to categorise. These social and economic vagaries of human interaction necessarily elude clean binary categorisations between the permissible and the impermissible.